2023
DOI: 10.12688/wellcomeopenres.16282.2
|View full text |Cite
|
Sign up to set email alerts
|

Acknowledging the gap: a systematic review of micronutrient supplementation in infants under six months of age

Abstract: Background: Micronutrient deficiencies remain common worldwide, but the consequences to growth and development in early infancy (under six months of age) are not fully understood. We present a systematic review of micronutrient interventions in term infants under six months of age, with a specific focus on iron supplementation. Methods: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (Ovid) and Embase (Ovid) from January 1980 through December 2019. Interventions included iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Most previous trials investigating the outcomes of early iron supplementation started supplementation at 3 to 4 months of age and assessed haemoglobin or ferritin or both. 19 Other trials recruited children aged between 1 and 36 months, but did not analyse outcomes separately for the youngest children. 20 , 21 However, one trial in north-east India found that, compared with no iron supplementation, starting supplementation (2 mg/kg as ferrous ascorbate) 36 hours after birth was associated with higher mean haemoglobin (97.0 versus 103.7 g/L, respectively; P < 0.0001) and ferritin (78 versus 134 microgram/L, respectively; P < 0.001) levels at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous trials investigating the outcomes of early iron supplementation started supplementation at 3 to 4 months of age and assessed haemoglobin or ferritin or both. 19 Other trials recruited children aged between 1 and 36 months, but did not analyse outcomes separately for the youngest children. 20 , 21 However, one trial in north-east India found that, compared with no iron supplementation, starting supplementation (2 mg/kg as ferrous ascorbate) 36 hours after birth was associated with higher mean haemoglobin (97.0 versus 103.7 g/L, respectively; P < 0.0001) and ferritin (78 versus 134 microgram/L, respectively; P < 0.001) levels at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of infants 3-5 months old in Indonesia found that the associated factors for anaemia were maternal anaemia, low birth weight and child stunting (12) . In contrast, feeding practices such as micronutrient supplementation have been found to be protective against early childhood anaemia (16)(17)(18) , and the WHO recommends iron supplementation starting as early as 2 months for infants with low birth weight (3) .…”
mentioning
confidence: 99%